On the Thermal Transformation of All-trans-1,6-Diphenyl-1,3,5-hexatriene (All-trans-DPH) into Its s-cis Conformer (s-cis-DPH) in Solution - Javier Catalán (Liquids)
The behavior of the energy of the peaks of the first UV/Vis absorption band and the presence or absence of isosbestic points in this band with changing temperature for all-trans-DPH and all-trans-β-carotene, dissolved in 1-chlorobutane or hydrocarbon solvents, allows us to show conclusively whether these compounds transform their all-trans-molecular structures into a structure of their conformers. From these analyses, it is concluded that in these solvents, all-trans-DPH is not thermally transformed to its conformer s-cis-DPH in a temperature range from 133 K to 350 K. On the other hand, all-trans-β-carotene, as a model-compound, does show changes in its molecular structure in these solvents with changing temperature. We also show that a portion of all-trans-DPH dissolved in cis-Decalin, at room temperature, slowly transforms into its conformer s-cis-DPH.